![](/img/avatar.jpg)
Срочноооооооооо,решение
![](/img/avatar.jpg)
(1) х=корень (a^2+b^2-2×a×b×cos a)=корень (64+75-2×8×5×(корень 3)×(корень 3)/2)=корень 19; (2) х=корень (a^2+b^2-2×a×b×cos a)=корень (25+32-2×5×4×(корень 2)×(1/корень 2))=корень (25+32-40)=корень 17
Оцени ответ
Вход
Регистрация
Задать вопрос
(1) х=корень (a^2+b^2-2×a×b×cos a)=корень (64+75-2×8×5×(корень 3)×(корень 3)/2)=корень 19; (2) х=корень (a^2+b^2-2×a×b×cos a)=корень (25+32-2×5×4×(корень 2)×(1/корень 2))=корень (25+32-40)=корень 17